Risk factors for incidence of rotator cuff syndrome in a large working population - Bodin, Julie; Ha, Catherine; Petit Le Manac’h, Audrey; Sérazin, Celine; Descatha, Alexis; Leclerc, Annette; Goldberg, Marcel; Roquelaure, Yves (Scandinavian Journal of Work, Environment & Health, 2012)
' ' OBJECTIVES ': 'The aim of this study was to assess the effects of personal and work-related factors on the incidence of rotator cuff syndrome (RCS) in a large working population. ' ' METHODS ': 'A total of 3710 French workers were included in a cross-sectional study in 2002–2005. All completed a self-administered questionnaire about personal factors and work exposure. Using a standardized physical examination, occupational physicians established a diagnosis of RCS. Between 2007–2010, 1611 workers were re-examined. Associations between RCS and risk factors at baseline were analyzed by logistic regression. ' ' RESULTS ': 'A total of 839 men and 617 women without RCS at baseline were eligible for analysis. RCS was diagnosed in 51 men (6.1%) and 45 women (7.3%). The risk of RCS increased with age for both genders [odds ratio (OR) 4.7 (95% confidence interval [95% CI] 2.2–10.0) for men aged 45–49 years and 5.4 (95% CI 2.3–13.2) for women aged 50–59 years; reference <40 years]. For men, the work-related risk factors were repeated posture with the arms above the shoulder level combined with high perceived physical exertion [OR 3.3 (95% CI 1.3–8.4)] and low coworker support [OR 2.0 (95% CI 1.1–3.9)]. For women, working with colleagues in temporary employment [OR 2.2 (95% CI 1.2–4.2)] and repeated arm abduction (60–90°) [OR 2.6 (95% CI 1.4–5.0)] were associated with RCS. ' ' CONCLUSIONS ': 'Age was the strongest predictor for incident cases of RCS, and arm abduction was the major work-related risk factor for both genders. Lack of social support was a predictor for RCS among men.
Keywords: incidence; MSD; musculoskeletal disease; occupational factor; personal risk factor; RCS; risk factor; rotator cuff syndrome; shoulder; tendinitis; work; working population